2017
DOI: 10.1016/j.conbuildmat.2017.04.060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of random porosity field on supercritical carbonation of cement-based materials

Abstract: Abstract:In this paper, the supercritical carbonation process of cement-based materials is modelled by introducing a random porosity field to simulate the heterogeneous geometry of the carbonation profile. The suitability of two different random fields of porosity, based on the Probability Density Function (PDF) and the Ellipsoidal Autocorrelation Function (EAF) methods, are investigated, respectively, in simulating the distribution of porosity in cement mortar. After incorporating the above random fields into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…Carbonation depth is one of the most important characteristics that are used to define the extent of the chemical process taken place during carbonation. Experimental research has shown that under both natural [23] and supercritical [3,24] conditions, the boundary topography of a carbonation zone is irregular, characterized by a random distribution of depth along the boundary with distinctive maximum and minimum. However, current theoretical and numerical models are almost exclusively based on the assumption that the materials are isotropic and homogenous [25] , resulting in an uniform carbonation depth [26] .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Carbonation depth is one of the most important characteristics that are used to define the extent of the chemical process taken place during carbonation. Experimental research has shown that under both natural [23] and supercritical [3,24] conditions, the boundary topography of a carbonation zone is irregular, characterized by a random distribution of depth along the boundary with distinctive maximum and minimum. However, current theoretical and numerical models are almost exclusively based on the assumption that the materials are isotropic and homogenous [25] , resulting in an uniform carbonation depth [26] .…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that that it was the heterogeneity of cement-based materials that contributes mostly to the observed randomness [29] . This includes the presence of coarse aggregates [30,31] , the carbon dioxide gas diffusion paths caused by distribution of cracks [31,32] and the randomly distributed porosity of cement mortar [24] . To study the irregularity of carbonation depth, Huang, et al [27] found that the variation of carbonation depth increased with increased use of coarse aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations